2015
DOI: 10.1002/jsfa.7344
|View full text |Cite
|
Sign up to set email alerts
|

The influence of post‐mortem conditioning on the tenderness of Egyptian goose (Alopochen aegyptiacus) breast meat (M. pectoralis major)

Abstract: No significant change (decline) in shear force values was observed. Conditioning of Egyptian goose meat as a means of improving the overall toughness cannot therefore not be proposed. The higher shear force and lower sensory tenderness of the male breast portions, as previously observed, may be linked to higher concentrations of total and insoluble collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The effect of aging on total collagen content has not been confirmed by Kołczak et al (2008) in bovine semitendinosus and psoas major muscles. In turn, Geldenhuys et al (2016) found a significant increase in total collagen in the pectoralis major muscle in geese after 14 d of aging compared to not aged meat. The differences in the total collagen content depending on the type of muscle in lamb meat were noted by Tschirhart-Hoelscher et al (2006).…”
Section: Chemical Composition Of Meatmentioning
confidence: 80%
“…The effect of aging on total collagen content has not been confirmed by Kołczak et al (2008) in bovine semitendinosus and psoas major muscles. In turn, Geldenhuys et al (2016) found a significant increase in total collagen in the pectoralis major muscle in geese after 14 d of aging compared to not aged meat. The differences in the total collagen content depending on the type of muscle in lamb meat were noted by Tschirhart-Hoelscher et al (2006).…”
Section: Chemical Composition Of Meatmentioning
confidence: 80%
“…Similar to the present study, Ablikim et al [8] observed a higher collagen content in the longissimus dorsi muscle compared to the GM muscle in Chinese sheep. In contrast, a higher proportion of collagen in goose breast muscle after 14 days of aging than in fresh meat was determined by Geldenhuys et al [43]. Differences in the content of this component depending on the type of muscle may be influenced by differences in the amount of intramuscular fat.…”
Section: Discussionmentioning
confidence: 86%
“…The shear force results obtained for Vištinės geese in the present study are in contrast with the shear force data values found in the Huoyan goose study [ 49 ] with a higher thigh WBSF. The effect of genotype on WBSF was reported by different authors [ 21 , 50 , 51 , 52 ]. In the present study, the sex did not show any effect on WB parameters, and this is in agreement with the data obtained for Yangzhou geese [ 24 , 47 ], whereas some other authors [ 50 , 52 ] have reported about the obtained sex effect on WBSF.…”
Section: Resultsmentioning
confidence: 94%
“…The effect of genotype on WBSF was reported by different authors [ 21 , 50 , 51 , 52 ]. In the present study, the sex did not show any effect on WB parameters, and this is in agreement with the data obtained for Yangzhou geese [ 24 , 47 ], whereas some other authors [ 50 , 52 ] have reported about the obtained sex effect on WBSF.…”
Section: Resultsmentioning
confidence: 94%